Lenguaje oral en niños de 3, 4 y 5 años de una institución educativa pública : distrito - Callao - Asian Suárez, Pilar Cristina (2010)
The purpose of this research was to determine the level of oral language proficiency (OL) in the phonological, syntactic and pragmatic areas. The students were evaluated using the revised version of the Navarra oral language test (Aguinaga, Armentia, Fraile, Olangua y Uriz, 2006). The sample was 208 3-5 year old children coming from a low socioeconomic class family and studying at a public school in Callao. The research results show that the children involved in the study have a low level of oral language (OL) and that there are no significant differences in this level between genders. It is suggested that a study be carried out to clearly identify the factors influencing the low level of oral language proficiency in these children.